Pengaruh discharge planning terhadap pengetahuan ibu dalam penanganan diare pada anak - Alfina Eka Saputri; Yuli Lestari; Annisa Agata (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: Discharge planning is a process where patients begin receiving health services followed by continuity of care both in the healing process and maintaining their health level until the patient feels ready to return to their environment. Purpose: To determine the effect of discharge planning on maternal knowledge in handling diarrhea in children. Method: Quantitative research and the design used is pre-experimental one group pre-post test design. The sample in this study were mothers of children who were treated for more than 3 days, in January and February as many as 33 people using accidental sampling. The analysis used was the Wilcoxon test. Results: Research analysis using the Wilcoxon Test found that there was an effect of discharge planning on maternal knowledge in handling diarrhea in children, where the p-value was 0.019 (p <0.05). Conclusion: There is a significant influence of discharge planning on mothers' knowledge in handling diarrhea in children after discharge planning was carried out on mothers.